DISTRIBUSI SPASIAL GENANGAN AIR LAUT BERDASARKAN ANALISIS DATA SATELIT ALTIMETRI ENVISAT DI WILAYAH PESISIR BARAT KABUPATEN BULELENG, BALI - Sriartha, I Putu; Eka Putra, I Wayan Krisna (Bumi Lestari, 2016)
This research was conducted in the western coastal region of Buleleng which includes two districts, namely: Seririt District and Gerokgak District. The research aims were (1) to analyze the trend of the dynamics of sea level in the period of 2002 to 2010, and (2) to predict the spatial distribution of flood of sea water. The data used are Envisat satellite altimetry data from the results of post-processing data, which were then analyzed the trend of mean sea level and forecast of sea level rise for year 2020 using linear regression analysis. To determine the spatial distribution of area flood of sea water, then the data of level rise forecast were analyzed with Geographic Information System (GIS). The results of this research define that the functional relationship of the trend of mean sea level rise in the area of research is y = 0.051 x + 1.612. The prediction of mean sea level rise that is obtained every year 5.1 cm and for 2020, the sea level rise is predicted to reach 2,224 cm. The width of coastal area that is potentially flooded of sea water reaches 812.954 m2 (0.227%). Spatially, the widest food area is Pejarakan village and the narrowest is Celukan Bawang village. The percentages of the villages that are flooded to area villages show a relatively homogeneousdistribution.
Keywords: Trend of mean sea level (MSL), spatial distribution of flood of coastal area